BIOACTIVE ACTIVITY OF A RECOMBINANT LONGAN (Dimocarpus longan LOUR.) SEED PEPTIDE - Thanaporn Wichai; Ruethairat Boonsombat (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Consumption of antioxidants has been evident to prevent diseases caused by free radicals damage. Antioxidants can be found in the form of peptide in various natural sources. From our previous study, to overcome obstacles of direct longan seed hydrolysate extraction, the recombinant Longan1 peptide which contains 4 repeats of ISYVVPVYIAEITPKTFRGGF linked by D was produced from Escherichia coli. The in vitro bioactive properties of this recombinant peptide were characterized. Methods: The recombinant and chemically synthesized Longan1 peptides were tested for bioactive activity including, DPPH, ABTS, and nitric oxide radical scavenging assays, the ability to protect plasmid DNA from hydroxyl radicals, anti-proliferative activity to several cancer cell lines, and antiinflammatory effects in cell culture level. Results: The recombinant peptide revealed antioxidative activities, including DPPH, ABTS, and nitric oxide radical scavenging activity, which are similar to the chemically-synthesized one. However, the recombinant peptide exhibited higher in vitro ability to protect DNA from hydroxyl radicals. The IC50 value of the recombinant Longan1 peptide could only be calculated through the assay of antiproliferation of stomach KATO-III cancer cell line, while IC50 value from the chemically synthesized peptide could not be calculated in any tested cell lines. Finally, the anti-inflammatory effect determined by the inhibition of nitric oxide production from macrophages RAW 264.7 activated by LPS revealed that the recombinant Longan1 peptide could inhibit nitric oxide production from macrophage cells, whereas the chemically-synthesized one could not. Conclusion: With all these properties, the recombinant Longan1 peptide seems to have bioactivity that can possibly be a candidate for further medical application or supplementary products.